Composite Performance Index in Decision Making for Social Assistance - Wulandari, Andini; Fakhriza, M. (Sinkron : jurnal dan penelitian teknik informatika, 2024)
The majority of the residents in this village, approximately 90%, worked as farmers or farm laborers. Given the economic conditions, social assistance became crucial in reducing social inequality and enhancing the welfare of vulnerable communities. The role of village governance was significant in improving community welfare. The Village Hall served as the center of village administration, managing various activities, including the distribution of social assistance. The Village Hall was responsible for ensuring that social assistance was distributed fairly and effectively to recipients according to prevailing policies. However, the Village Hall faced issues such as inefficiency and inequality in the distribution of social assistance. The process of selecting social assistance recipients was still conducted conventionally, where Village Hall staff collected data on the community based on certain criteria. This method was prone to errors in decision-making and incorrect distribution of assistance, such as recipients who did not actually qualify still receiving aid, while those in need often did not receive appropriate support. These issues were caused by a lack of thorough analysis. The village government needed to establish a decision-making system that was accurate and precise. The operation of this system included all steps of problem identification, selection of relevant information, and determination of the approach used for decision-making through to the resolution of the issues. To achieve accurate results, this research applied the Composite Performance Index method. The aim of this research was to create a decision support system (DSS) for selecting social assistance recipients in the village. This DSS was expected to help staff improve the speed of social assistance classification, avoid errors, and produce accurate decisions.